2019
DOI: 10.1080/13662716.2019.1633278
|View full text |Cite
|
Sign up to set email alerts
|

Regulation strictness and supply in the platform economy: the case of Airbnb and Couchsurfing

Abstract: To what extent is regulation associated with supply in the platform economy (PE)? We address this research question by analyzing the relationship between the strictness of rules/laws in 59 U.S. cities and the number of short-stay accommodation offerings. We find that the stricter regulation is, the higher the supply in these platforms. We also investigate how the presence (or lack thereof) of money transactions in the platform affects this relationship. We discover that the presence of money transactions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Recently, the concerns regarding the disruptive power of both for-profit and nonprofit P2P accommodations for hotels and governments highlight a need for setting and reinforcing new regulations and standards (Dalir et al, 2020). Uzunca and Borlenghi (2019b) stressed about the necessity of regulations and the strictness on the supply side for Airbnb and couchsurfing and concluded that regulating strictness can positively raise the demand for the P2P accommodations by reducing the uncertainty. Even when the strictness has a negative impact on the demand, free P2P accommodations are less affected by legislation because of their nature, which is based on sharing and reciprocity.…”
Section: Non-profit P2p Accommodation (Couchsurfing)mentioning
confidence: 99%
“…Recently, the concerns regarding the disruptive power of both for-profit and nonprofit P2P accommodations for hotels and governments highlight a need for setting and reinforcing new regulations and standards (Dalir et al, 2020). Uzunca and Borlenghi (2019b) stressed about the necessity of regulations and the strictness on the supply side for Airbnb and couchsurfing and concluded that regulating strictness can positively raise the demand for the P2P accommodations by reducing the uncertainty. Even when the strictness has a negative impact on the demand, free P2P accommodations are less affected by legislation because of their nature, which is based on sharing and reciprocity.…”
Section: Non-profit P2p Accommodation (Couchsurfing)mentioning
confidence: 99%
“…Indeed, platform economy organizations have been subject to criticism and restrictions from regulators (Hinings et al, 2018) as they deviate from existing categories. For instance, home‐sharing platform Airbnb has been criticized for the inconvenience created for neighbours, unfair competition and rising real estate prices, inciting new regulations such as limits to the number of days that homes can be rented (Uzunca and Borlenghi, 2019; Uzunca et al, 2018). Labour platforms (e.g., Uber, Deliveroo) that offer flexible working hours have been chastised for creating a new category of low‐income labourers, shifting risk to workers (e.g., no sick pay) and generating job insecurity (Davis, 2016; O’Keefe and Jones, 2015; Petriglieri et al, 2019; Rogers, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, as we mentioned before, the limited literature about other forms of P2P accommodation enabled us only to compare the most common topics found between Couchsurfing and Airbnb. The data on Couchsurfing were based on the review article by Prayag and Ozanne (2018) and the WoS core collection articles (Uzunca and Borlenghi, 2019; O’Regan and Choe, 2019; Chen, 2018; Decrop et al , 2018; Chen, 2017; Luo and Zhang, 2016; Lampinen, 2016; Germann Molz, 2013; Rosen et al , 2011). As can be observed in Table III, seven common topics studied in the Couchsurfing literature were found.…”
Section: Most Common Topics Studied On Airbnb and Other Peer-to-peer Platformsmentioning
confidence: 99%